Amino Acid-Containing Krebs-Henseleit Buffer Protects Rat Liver in a Long-Term Organ Perfusion Model - Reza Heidari; Mohammad Mehdi Ommati; Sanya Alahyari; Negar Azarpira; Hossein Niknahad (Tabriz University of Medical Sciences, 2018)
Background: The liver is vulnerable to the toxicity induced by xenobiotics. On the other hand, it has been found that several endogenously-found amino acids have hepatoprotective properties. The current study was designed to evaluate the effect of taurine, glycine, and histidine on the liver function in an ex vivo model of prolonged organ perfusion. Methods: Rat liver was isolated and perfused with a hemoglobin- and albumin-free Krebs-Henseleit buffer (KBH). Liver injury biomarkers were monitored at scheduled time intervals. Results: The perfusate level of lactate dehydrogenase (LDH), alanine aminotransferase (ALT), aspartate aminotransferase (AST), and the potassium ion (K+) were gradually increased in control (Only KBH) group. The histopathological evaluation also revealed significant necrosis, sinusoidal dilation, and pyknosis in control liver. Moreover, significant increase in lipid peroxidation and depletion of hepatic glutathione stores were detected in the control group. It was found that taurine (5, 10 and 20 mM) and glycine (5, 10 and 20 mM)-containing KBH buffer significantly decreased the perfusate level of liver injury biomarkers. Furthermore, lower liver tissue pathological changes, decreased lipid peroxidation, and higher glutathione content was detected in amino acid-treated groups. Histidine administration showed no significant protective effect on liver injury in the current study. On the other hand, combination amino acid administration (glycine and taurine) showed a better hepatoprotective profile. Conclusion: The data obtained from the current study might help to provide safe hepatoprotective agents against xenobiotics-induced hepatotoxicity or preserve liver functionality outside the body.